A motivation perspective on achievement appraisals, emotions, and performance in an online learning environment. (2021) - Parker, Patti C.; Perry, Raymond P.; Hamm, Jeremy M.; Chipperfield, Judith G.; Pekrun, Reinhard; Dryden, Robert P.; Daniels, Lia M.; Tze, Virginia M.C.
Highlights: Motivation profiles based on control-value theory were examined. The profiles comprise academic control and value appraisals and achievement emotions. Findings show the nature of multifaceted motivation profiles that predict achievement. Abstract: Control-value theory (CVT) posits that cognitive appraisals and emotions govern motivation and learning in achievement settings. Within this framework, we used latent profile analysis to identify multifaceted motivation profiles involving academic control and value appraisals and achievement emotions (boredom, anxiety, enjoyment). Three motivation profiles were identified that comprised co-occurring appraisals and emotions at the start of a two-semester online university course: high control-enjoyment, low control-boredom, low value-boredom . These motivation profiles related to achievement perceptions and performance on six tests over the two-semester introductory psychology course. High control-enjoyment students reported greater success and expected better grades than low control-boredom and low value-boredom students, and outperformed low control-boredom students on all tests. These findings document the nature of adaptive (vs. maladaptive) CVT-related motivation profiles that predict academic attainment in an online course.